Evaluasi Anggaran Berbasis Kinerja, SPIP, dan Akuntabilitas Kinerja di Pemerintah Kabupaten Manggarai Timur: Studi Kasus Badan Keuangan Daerah Kabupaten Manggarai Timur - Mariana Natalia Tri De Wieke Jiman; Anthon Simon Y. Kerihi; Minarni A. Dethan (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze and explain the implementation of performance-based budgeting, the Government Internal Control System (SPIP), and government performance accountability in the East Manggarai Regency Regional Government, with a case study conducted at the East Manggarai Regency Regional Finance Agency. The research uses a descriptive qualitative method to explore how these three aspects are integrated and applied in the regional financial management system. The findings reveal that the implementation of performance-based budgeting has brought fundamental improvements in financial governance. Budget planning and fund allocation are now more prioritized, economical, efficient, and transparent, supported by a structured and accountable budget presentation system. Furthermore, the implementation of the Government Internal Control System (SPIP) has generally shown positive outcomes in the management of public resources. This is demonstrated by a strong commitment to integrity, consistent risk evaluation, an integrated control system based on the Regional Development Information System (SIPD), effective communication mechanisms, and thorough monitoring processes. In addition, the performance accountability of the East Manggarai Regency Regional Finance Agency has also improved, as evidenced by regular performance evaluations, participative budgeting processes, and the collaborative establishment of performance indicators. These efforts reflect a growing culture of transparency, accountability, and efficiency in the governance of regional finances. Overall, the integration of performance-based budgeting, SPIP, and accountability mechanisms has contributed significantly to improving the quality of public financial management in the region, indicating a positive trajectory towards good governance in the public sector.